THE RELATIONSHIP BETWEEN MARKET PRESSURE AND THE EXTENT OF BIODIVERSITY DISCLOSURE - Ni Putu Stefy Chaterina Wijaya; Putu Agus Ardiana (CV. Adiba Aisha Amira, 2025)
This study aims to examine the association between market pressure and the extent of biodiversity disclosure among companies across all sectors listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A total of 990 sustainability reports published by these companies within the same period were analysed. Content analysis was employed to measure the extent of biodiversity disclosure as the dependent variable, while market pressure served as the independent variable. This study used Institutional theory to explain the association between the variables. Pearson correlation and multiple linear regression analyses were conducted to investigate both simple and more complex relationships, specifically the association between non-Asian market pressure and the extent of biodiversity disclosure. The results indicate a positive relationship, suggesting that companies tend to respond to institutional pressures from non-Asian markets by increasing transparency in biodiversity disclosure to maintain legitimacy and a good reputation in the international market.